Understanding Academic Research Plan: An Overview - Basturi Hasan (Universitas Lampung, 2017)
The goal of all scientific studies is to explain, predict, and control phenomena. The goal is based on assumption that all behaviors and events are orderly and that they are effects which have discoverable causes. Progress toward this goal involves acquisition of knowledge and the development of testing of theories. Dealing with this idea, typical research traditions are exposed in this article aimed at providing insights for the students in order to become knowledgeable about how to systematically and logically construct academic research plan.Key words: research components, concept and variable, research traditions